Vključenost slovenskega družboslovja in humanistike v Web of Science in Scopus - Čadej, Robert (Knjižnica, 2015)
Web of Science and Scopus are considered to be two of the largest citation databases in the world. They are important in terms of access to the world's scientific literature and in terms of research quality control mechanisms at the national level. The aim of this study was to determine which of the two databases better represents Slovenian research output in social sciences and humanities, and where the journals achieve better rankings. Using Slovenian Current Research Information System (SICRIS) and online versions of WoS and Scopus, we analysed articles and received citations of the selected sample of researchers (researchers with most SICRIS points). The results confirmed the initial hypothesis that the Scopus outperforms WoS in published publications in the field of social sciences and humanities and received more citations. Journals also receive higher rankings in Scopus. The findings suggest that Scopus is the preferred tool for national scientific evaluation in the fields of social sciences and humanities in Slovenia and that in the future we need to pay more attention to the use of Scopus in these two areas.
Keywords: podatkovne baze; indeksi citiranja; družboslovje; social science; humanistika; Web of Science; Scopus; znanstvene revije; citiranost; vrednotenje raziskovalnega dela